Taking stock: the customs union between Turkey and the EU fifteen years later - Kamil Yilmaz (TÜSİAD-Koç University Economic Research Forum, 2010)
This article focuses on the customs union (CU) already in effect for almost a decade and a half now and links the impact of the CU with the sources of support as well as resistance within Turkey to further integration with the EU. Overall the CU had a positive impact on Turkish economy through improved productivity in manufacturing industries. While the increased import penetration after the CU increased the competitive pressure on several industries in the short run, this short-run impact helped them improve productivity in the medium- to long-term. The CU also led to significant improvements in the implementation of competition policy with additional positive effects on Turkish economy. With increased productivity and competitiveness manufacturing industries was able to weather the storm during 2001 economic crisis and in the wake of Chinese entry to world export markets. However, following the successful initial adaptation phase and the significant changes in the EU's trade policy framework towards preferential trade agreements, the CU has started to generate some strains on Turkish trade.
Keywords: F14; 330; Turkey; European Union; Customs Union; Free Trade Area; Welfare analysis; Computable General Equilibrium; Exports; Imports; Europäische Wirtschafts- und Währungsunion; Freihandelszone; Wohlfahrtseffekt; Allgemeines Gleichgewicht; Türkei